Single-atom engineering of metal-organic frameworks toward healthcare - Wang, Dongdong (2022)
Single-atomic nanocatalysts/nanozymes (SACs/SAEs) have emerged as a research frontier on account of the maximum atom-utilization efficiency and well-defined localized structure. Metal-organic frameworks (MOFs) featuring the structural diversity and functional tunability are promising host materials in constructing SACs/SAEs. Further pyrolysis of MOF precursors under certain conditions can lead to the formations of MOF-derived SACs/SAEs. In this review, we first introduce the classification and enzymatic mechanisms of nanozymes, comprehensive characterization techniques for SACs/SAEs, and various synthetic methodologies of MOF-based SACs/SAEs. Next, we highlight the recent advances of MOF-based SACs/SAEs in the enzymatic healthcare area, i.e., cancer treatment, biosensing, anti-bacteria, reactive oxygen species scavenger, and environmental protection. Finally, we summarize the insights we gain from these studies, and discuss possible design principles and future challenges for a deeper understanding of this emerging field, thus offering great opportunities to leap over conventional nanozymes into a new era of next-generation biosafe SACs/SAEs.